Mental Wellbeing among Children with Cancer during COVID-19 Pandemic in Indonesia: A Cross-sectional Study - Teny Tjitra Sari; Tjhin Wiguna; Sylvia Detri Elvira; Indah Suci Widyahening; Rinoldy Mangiri; Apul S. Napitupulu; Nathania Sutandi; Silvia Tanumiharjo; R S. Sitorus (Indian Journal of Medical and Paediatric Oncology)
Introduction Coronavirus disease 2019 (COVID-19) has affected both physical and mental aspect of people worldwide, especially the high-risk group such as pediatric cancer patients. Children with cancer were considered both clinically and mentally vulnerable during this pandemic. They were also affected by the self-isolation, quarantine, and social distancing policy taken as a respond to public threat.